Legal Vacuum in the Deferred Prosecution Agreement Mechanism for Corporations Perpetrating Forestry Crimes for the Reform of the Criminal Justice System - Deki Hermika; Richard (Journal of Legal and Cultural Analytics, 2026)
This study analyzes the legal vacuum concerning the Deferred Prosecution Agreement (DPA) mechanism for corporations committing forestry crimes and formulates a reconstruction of criminal law policy in Indonesia. Using a normative juridical approach, this research examines the Criminal Code, Criminal Procedure Code, Law Number 18 of 2013, Law Number 32 of 2009, and Supreme Court Regulation Number 13 of 2016. The findings show that although corporate criminal liability has been recognized, conventional law enforcement remains ineffective due to evidentiary difficulties, procedural limitations, and inadequate environmental restoration mechanisms. The DPA concept offers a more efficient and restorative approach by emphasizing corporate compliance, compensation, and environmental recovery. However, the absence of explicit regulation creates legal uncertainty. Therefore, legal reform is needed to incorporate DPA mechanisms into the national legal system while upholding the principles of legality, due process of law, and environmental accountability to strengthen law enforcement and sustainable forest protection.